PREPARATION OF IBRUTINIB-LOADED NANOSUSPENSION: IN VITRO AND IN VIVO PHARMACOKINETIC EVALUATION FOR ENHANCED DISSOLUTION AND BIOAVAILABILITY - VALLABH DEULKAR; PATHURI RAGHUVEER (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of this study was to develop and optimize an ibrutinib (IBR) nanosuspension (NS) formulation using the wet media milling technique and to evaluate its pharmacokinetic (PK) performance in comparison with the plain drug (PD) formulation under both fed and fasted conditions. Methods: The IBR NS was formulated using a wet nano ball milling technique (Fritsch Pulverissette 7, Germany) with stabilizers such as Tween 80, sodium lauryl sulfate, and hypromellose. The optimized formulation was further processed using spray drying. The formulation was characterized for size, potential, and polydispersity using dynamic light scattering. The Fourier-transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction, and scanning electron microscopy techniques were employed for physicochemical characterization. Saturation solubility, dissolution, and stability studies were conducted to assess the formulation’s performance. PK studies were performed on the IBR NS and PD (IBR PD) formulations in both fed and fasted conditions to evaluate key parameters such as Cmax, Tmax, half-life, area under the curve (AUC0–∞), and mean residence time. Results: After spray drying, the IBR NS showed a notably lower particle size of 135.6 nm with a polydispersity of 0.389 and a zeta potential of −27.1 mV. The formulation showed a 3.786-fold surge in Cmax and a 2.996-fold rise in AUC0–24 h in comparison to the drug in fasting conditions. The IBR NS maintained consistent PK characteristics across fed and fasted conditions, demonstrating improved bioavailability. Saturation solubility experiments also indicated a 12.96-fold rise in solubility for the IBR NS versus to the typical medication. Conclusion: The IBR NS formulation exhibited enhanced solubility, stability, and bioavailability compared to the PD formulation. The significant increase in PK parameters such as Cmax and AUC0–24 h underscores the potential of NS technology in proving the p.o bioavailability of poorly soluble drugs. This formulation can provide a more reliable therapeutic effect and has the potential for further clinical application in the treatment of chronic conditions.